2023
DOI: 10.3390/biology12030346
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of GJC1 (Cx45) as a New Gene Underlying Congenital Heart Disease and Arrhythmias

Abstract: As the most prevalent type of birth malformation, congenital heart disease (CHD) gives rise to substantial mortality and morbidity as well as a socioeconomic burden. Although aggregating investigations highlight the genetic basis for CHD, the genetic determinants underpinning CHD remain largely obscure. In this research, a Chinese family suffering from autosomal dominant CHD (atrial septal defect) and arrhythmias was enrolled. A genome-wide genotyping with microsatellite markers followed by linkage assay as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Here we showed that Cx26 was able to form functional GJ channels in DKO HEK293 cells and in some cases with only one or two channels between a cell pair providing an excellent vehicle to study mechanistic defects associated Cx26 mutants in individual GJ channels. Expression of a congenital heart disease and arrhythmia linked mutation in Cx45 (R184G) in DKO HEK293 cells resulted in no functional GJ formed, similar to that observed in N2A cells [53]. The failure to cluster at the cell-cell junctions of Cx45 R184G in DKO HEK293 cells was also observed in HeLa cells (Chen and Bai unpublished observations).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Here we showed that Cx26 was able to form functional GJ channels in DKO HEK293 cells and in some cases with only one or two channels between a cell pair providing an excellent vehicle to study mechanistic defects associated Cx26 mutants in individual GJ channels. Expression of a congenital heart disease and arrhythmia linked mutation in Cx45 (R184G) in DKO HEK293 cells resulted in no functional GJ formed, similar to that observed in N2A cells [53]. The failure to cluster at the cell-cell junctions of Cx45 R184G in DKO HEK293 cells was also observed in HeLa cells (Chen and Bai unpublished observations).…”
Section: Discussionmentioning
confidence: 67%
“…To reveal the mechanism of a congenital heart disease and arrhythmia linked Cx45 variant R184G [53], we expressed this variant in DKO HEK293 cells in two expression vectors, i.e. GFP untagged Cx45 R184G-IRES-GFP and GFP tagged Cx45 R814G-GFP for functional and morphological studies respectively.…”
Section: Human Congenital Heart Disease and Arrhythmia Linked Cx45 Va...mentioning
confidence: 99%
“…In general, more than 50% of all CHD cases still fall into the unknown category [ 28 ]. Most cases with known etiology are believed to be caused by genomic abnormalities, including mutations in genes important for heart development such as transcription factors [ 29 ] or structural heart genes [ 30 ], but also maternal environmental factors such as diabetes [ 31 ], a high-fat diet [ 32 ], ethanol abuse [ 33 ] or exposure to other teratogens including prenatal viral infections (recently reviewed in [ 28 ]). The defects of atrial septation, as noted in our case, are far more common in mammals than in other vertebrates, probably due to its higher complexity with primary and secondary septa [ 34 ].…”
Section: Discussionmentioning
confidence: 99%